2013
DOI: 10.3755/galaxea.15.379
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies on the 2010 mass coral bleaching event in Thai waters

Abstract: A severe coral reef bleaching event occurred in late summer 2010 in the Gulf of Thailand and the Andaman

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As this study aims to evaluate vulnerability to warming in shallow-water marine organisms, we focused on their stress responses to an increase in temperature within a range recorded in their natural settings encompassing the future warming scenarios. The testing temperatures were chosen based on past SST (27.45 ± 0.02 • C to 32.00 ± 0.02 • C, Figure 1B), records of temperature profiles of the sampling sites (28.84-30.25 • C in shallow water coral reefs and 26.96-36.70 • C in tidal flat areas at the respective sampling periods, Supplementary Table 1), our previous investigations (Rasmusson et al, 2020(Rasmusson et al, , 2021unpublished data) and other studies from the tropical shallow waters (Sutthacheep et al, 2013a;Pedersen et al, 2016;George et al, 2018;Kong et al, 2019). Extreme temperatures, exceeding 40 • C, have been reported in tropical seagrass meadows Pedersen et al, 2016;George et al, 2018) whereas the highest temperature reported in shallow water coral reefs in Thailand was 32.7 • C (Sutthacheep et al, 2013a).…”
Section: Experimental Designmentioning
confidence: 61%
See 1 more Smart Citation
“…As this study aims to evaluate vulnerability to warming in shallow-water marine organisms, we focused on their stress responses to an increase in temperature within a range recorded in their natural settings encompassing the future warming scenarios. The testing temperatures were chosen based on past SST (27.45 ± 0.02 • C to 32.00 ± 0.02 • C, Figure 1B), records of temperature profiles of the sampling sites (28.84-30.25 • C in shallow water coral reefs and 26.96-36.70 • C in tidal flat areas at the respective sampling periods, Supplementary Table 1), our previous investigations (Rasmusson et al, 2020(Rasmusson et al, , 2021unpublished data) and other studies from the tropical shallow waters (Sutthacheep et al, 2013a;Pedersen et al, 2016;George et al, 2018;Kong et al, 2019). Extreme temperatures, exceeding 40 • C, have been reported in tropical seagrass meadows Pedersen et al, 2016;George et al, 2018) whereas the highest temperature reported in shallow water coral reefs in Thailand was 32.7 • C (Sutthacheep et al, 2013a).…”
Section: Experimental Designmentioning
confidence: 61%
“…The testing temperatures were chosen based on past SST (27.45 ± 0.02 • C to 32.00 ± 0.02 • C, Figure 1B), records of temperature profiles of the sampling sites (28.84-30.25 • C in shallow water coral reefs and 26.96-36.70 • C in tidal flat areas at the respective sampling periods, Supplementary Table 1), our previous investigations (Rasmusson et al, 2020(Rasmusson et al, , 2021unpublished data) and other studies from the tropical shallow waters (Sutthacheep et al, 2013a;Pedersen et al, 2016;George et al, 2018;Kong et al, 2019). Extreme temperatures, exceeding 40 • C, have been reported in tropical seagrass meadows Pedersen et al, 2016;George et al, 2018) whereas the highest temperature reported in shallow water coral reefs in Thailand was 32.7 • C (Sutthacheep et al, 2013a). As corals are exposed to smaller thermal variations in situ compared to seagrasses and macroalgae (Supplementary Table 1), narrower range of temperature with smaller increment was thus adopted for coral experimental design.…”
Section: Experimental Designmentioning
confidence: 61%
“…Losin Pinnacle has a much higher species diversity, over 75 species, compared to other Thai reefs; 47 species were recorded from twelve sites in the Andaman Sea (Phongsuwan and Chansang, 2012), and only 44 species were recorded from six sites in the Gulf of Thailand (Yeemin et al, 2009;Sutthacheep et al, 2012Sutthacheep et al, , 2013. Though the overall area of the reef at Losin Pinnacle is relatively small, the coverage of live coral is high relative to other Thai reefs, which typically have live coral cover ranging from approximately 8% to 45% (Phongsuwan et al, 2013;Yeemin et al, 2013a;Sutthacheep et al, 2015). Additionally, Losin reef is rich in fish (111 species, personal communication), and other benthic organisms such as ascidians, octocorals, echinoderms, crustaceans, and sponges (Darumas et al, 2018;Marine and Coastal Resources Research and Development Institute, 2018).…”
Section: Discussionmentioning
confidence: 99%